Statutul cercetării științifice în România și UE - Mărginean, Ioan (Calitatea Vieții, 2007)
In Romania, the field of scientific research has an important development potential, which is only partially put into light, due to its poor status. This article is dedicated to the comparative analysis of two indicators descripting scientific research status in Romania and EU: the number of researchers and the financing.